Numerical Simulation of the Flow Field in Circumferential Grooved Liquid Seals - Meng Zhang; Xiao-fang Wang; Sheng-li Xu; Wei Wang (Advances in Mechanical Engineering, 2013)
Circumferential grooved liquid seals are utilized inside turbomachinery to provide noncontacting control of internal incompressible fluid leakage. Accurate prediction of the flow field is fundamental in producing robust and efficient designs. To validate the capabilities of the computational fluid dynamics FLUENT for incompressible fluid seal flow, comparisons of velocity parameters are made to the published experimental results and other CFD code for a circumferential grooved liquid seal. This work employs a pressure-based CFD code FLUENT to calculate the flow field in the seal, using four different turbulence models respectively. The velocity contours are compared with experimental values. It shows good overall agreement of the axial, radial, and azimuthal velocities in the through-flow jet, shear layer, and recirculation zone. Quantitative comparisons of velocity profiles at the center of the groove are made to experiment. This study verifies the prediction accuracy of three turbulence models. Various structures were considered to obtain a better understanding of the circumferential grooved liquid flow characteristics. The best groove structure to control leakage was also found within the limited designed seal. This study will provide a useful reference for designing the circumferential grooved liquid seal.